Effects of Dietary Astragalus Polysaccharide Supplementation on the Th17/Treg Balance and the Gut Microbiota of Broiler Chickens Challenged With Necrotic Enteritis - Song, Bochen; Li, Peng; Yan, Shaojia; Liu, Yan; Gao, Mingkun; Lv, Huiyuan; Lv, Zengpeng; Guo, Yuming (Frontiers in Immunology, 2022)
This study aimed to investigate the effects of dietary astragalus polysaccharide (APS) supplementation on the immune function, gut microbiota and metabolism of broiler chickens challenged with necrotic enteritis (NE). Two hundred forty Arbor Acres broiler chicks (one day old) were randomly assigned using a 2 × 2 factorial arrangement into two groups fed different levels of dietary APS (0 or 200 ppm of diet) and two disease challenge groups (control or NE challenged). The results showed that NE infection significantly increased FCR, mortality rate, Th17/Treg (Th17 cells% in blood and ileum, Th17/Treg, IL-17 and IL-17/IL-10 in blood), NO, lysozyme activity and IL-1β in blood, intestinal immune cell proportion and activity (Tc%, Treg% and monocyte phagocytic activity in ileum), intestinal inflammatory cytokines (TLR2, NF-κB, TNF-α and IL- 6) gene expression levels, and the number of Clostridium perfringens in cecum. NE infection significantly reduced body weight gain, thymus index, lymphocyte proliferation activity in blood and ileum, villus height and V/C in jejunum, Th cells% and Mucin2 gene expression in ileum. Dietary APS supplementation significantly increased body weight, feed intake, proportion of immune cells (T cells in blood and Tc, Treg in ileum), lymphocyte proliferation activity, V/C in jejunum, and ZO-1 gene expression in ileum. Dietary APS supplementation significantly reduced FCR and mortality rate, Th17/Treg, Th17%, intestinal pathology scores, intestinal inflammatory cytokine gene expression levels, and the number of Clostridium perfringens in cecum. In addition, broilers challenged with NE significantly increased Staphylococcus and Turicibacter and reduced α diversity of microbiota in ileum. Dietary APS supplementation significantly increased α diversity, Romboutsia, Halomonas, propionic acid, butyric acid, formononetin, taurine, cholic acid and equol and downregulated uric acid, L-arginine and serotonin in ileum. Spearman's correlation analysis revealed that Romboutsia, Turicibacter, Staphylocpccus, Halomonas, Streptococcus, Escherichia-Shigella, Prevotella, uric acid, L-arginine，jerivne, sodium cholate and cholic acid were related to inflammation and Th17/Treg balance. In conclusion, APS alleviated intestinal inflammation in broilers challenged with NE probably by regulating intestinal immune, Th17/Treg balance, as well as intestinal microbiota and metabolites.